An Investigation of Chromatographic Partitioning of CO2 and Multiple Impurities in Geological CO2 Sequestration. (August 2015) - Li, Didi; Jiang, Xi
Abstract: Different solubilities of CO2 and impurities contained in the injected streams would result in partitioning of the components at the leading gas front advancing through the aqueous phase. In this study, the chromatographic partitioning phenomena of CO2 with multiple impurities are investigated by numerical simulations. Three most common impurities, i.e., N2, H2 S and CH4, are selected and studied. Compared with the partitioning phenomenon of CO2 and H2 S, our simulation results indicate that, the inclusion of less soluble N2 and/or CH4 results in an earlier gas breakthrough and a longer delay between the breakthrough times of CO2 and H2 S. This is mainly because that the addition of N2 and/or CH4 lowers the viscosity of the gas phase, resulting in much higher gas mobility than that of the CO2 -H2 S mixture. Thus, gas mixture contacts with brine over a larger area, giving rise to more efficient stripping of H2 S.